2021
DOI: 10.3390/jpm11070661
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology and Targeted Therapies for Personalized Management of Central Nervous System Germinoma

Abstract: Intracranial germinomas are rare tumours, usually affecting male paediatric patients. They frequently develop in the pineal and suprasellar regions, causing endocrinological disturbances, visual deficits, and increased intracranial pressure. The diagnosis is established on magnetic resonance imaging (MRI), serum and cerebrospinal fluid (CSF) markers, and tumour stereotactic biopsy. Imaging techniques, such as susceptibility-weighted imaging (SWI), T2* (T2-star) gradient echo (GRE) or arterial spin labelling ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 162 publications
0
19
0
Order By: Relevance
“…Recurrence, however, is not uncommon, and protracted follow-up is advised [9]. In these instances, because the individual was already subjected to radiation, a combination of chemotherapy and radiation is strongly advised, as opposed to radiation therapy alone [10,11]. Furthermore, it has been suggested that even at its initial presentation, radiation should be limited to "reduced-volume-radiotherapy plus boost" instead of craniosacral radiotherapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence, however, is not uncommon, and protracted follow-up is advised [9]. In these instances, because the individual was already subjected to radiation, a combination of chemotherapy and radiation is strongly advised, as opposed to radiation therapy alone [10,11]. Furthermore, it has been suggested that even at its initial presentation, radiation should be limited to "reduced-volume-radiotherapy plus boost" instead of craniosacral radiotherapy [12].…”
Section: Discussionmentioning
confidence: 99%
“…The most common type of metastasis associated with germinomas are spinal “drop” metastasis. 27 Occurrence of these drop metastases synchronously with pineal germinoma is unusual, 50 although Lo et al find an incidence of synchronous presentation in 11% of pineal germinoma. 51 When these spinal metastases occur, symptoms may consist of low back pain, 52 monoparesis, 53 paraparesis, or quadriparesis or tetraparesis, 54 paresthesia, 55 numbness with a sensory level, spasticity, 54 and urinary retention.…”
Section: Diagnosismentioning
confidence: 99%
“…Symptoms which suggest hydrocephalus include headaches, nausea, projectile vomiting, and lethargy. 27 But because patients with papilledema can be asymptomatic, a fundoscopic exam is essential, regardless of symptoms.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Mature teratomas are usually treated with surgery, while the other NGGCTs are usually managed with a combination of surgery, chemotherapy, and radiotherapy depending on the tumor type. Molecular targeted therapy with inhibitors of KIT/RAS activation and the AKT1/mTOR pathway potentially represent promising therapeutic strategies [ 62 ]. Prognosis is usually good for germinomas and mature teratomas, while choriocarcinomas and embryonal carcinomas are often associated with a poorer outcome.…”
Section: Introductionmentioning
confidence: 99%